Gambling to leapfrog in status? - Tim Friehe; Mario Mechtel (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2014)
This paper shows that households with positional concerns and convex status utility use gambling to attempt leapfrogging in the social hierarchy. We test this theoretical prediction relying on household data that is representative for Germany, proxying the status orientation of households by their expenditures for conspicuous consumption. Our empirical results strongly indicate that households who care about status are more likely to participate in gambling and invest more in gambling, while they save less.
Keywords: D12; D14; D62; 330; conspicuous consumption; status; relative income; gambling; behavioral economics